Gene of the month: APOL1. Issue 8 (13th May 2020) - Raghubeer, Shanel; Pillay, Tahir S; Matsha, Tandi Edith
Abstract : Apolipoprotein L1 (APOL1) is a protein encoded by the APOL1 gene, found only in humans and several primates. Two variants encoding two different isoforms exist for APOL1, namely G1 and G2. These variants confer increased protection against trypanosome infection, and subsequent African sleeping sickness, and also increase the likelihood of renal disease in individuals of African ancestry. APOL1 mutations are associated with increased risk of chronic kidney disease, inflammation, and exacerbation of systemic lupus erythematosus-associated renal dysfunction. This review serves to outline the structure and function of APOL1, as well as its role in several disease outcomes.